Comparison of Efficacy and Safety of Intrauterine Balloon Tamponade Versus Uterovaginal Packing in Females Presenting with Postpartum Hemorrhage after Normal Vaginal Delivery - Agrawal, Subhadra; Munir, Shamila Ijaj (Nepal Medical College Journal, 2024)
To compare the efficacy and safety of intrauterine balloon tamponade with uterovaginal roll gauze packing in patients presenting with primary postpartum hemorrhage after normal vaginal delivery. This randomized controlled trial, conducted at Department of Obstetrics and Gynecology, Lady Willingdon Hospital, Lahore, from December 2015 to November 2016. Two hundred and twelve patients presenting with primary postpartum hemorrhage who did not respond to medical treatment following normal vaginal delivery were included. They were randomly divided in two groups. The first group underwent balloon tamponade using condom and second group underwent intrauterine packing using roll gauze. Both interventions were removed after 24 hours. All females were kept under observation with antibiotic coverage in ward to prevent infection. If bleeding was stopped within 15 minutes and the patient remained hemodynamically stable, then efficacy was labeled and if no complications occur while applying or removing, safety was labeled. Mean age group of women using balloon tamponade and intrauterine packing was used was 28.25±4.672 and 28.30±4.613 years. The mean gestational age of patients using balloon tamponade and intrauterine packing was 38.57±1.36 and 38.63±0.62 years. Mean blood loss in patients using balloon tamponade and intrauterine packing was 600.28±25.338 and 699.21±70.176 ml. Efficacy of intrauterine packing was 94 (88.7%) and balloon tamponade was 104 (98.1%). Safety of intrauterine packing was 83 (78.3%) and that of balloon tamponade was 97 (91.5%). Thus, treatment of balloon tamponade was more effective and safer than intrauterine packing in female presenting with postpartum hemorrhage after normal vaginal delivery.